Forkhead box A2 regulates biliary heterogeneity and senescence during cholestatic liver injury in mice‡. Issue 2 (5th November 2016) - McDaniel, Kelly; Meng, Fanyin; Wu, Nan; Sato, Keisaku; Venter, Julie; Bernuzzi, Francesca; Invernizzi, Pietro; Zhou, Tianhao; Kyritsi, Konstantina; Wan, Ying; Huang, Qiaobing; Onori, Paolo; et al.
Abstract : Biliary‐committed progenitor cells (small mouse cholangiocytes; SMCCs) from small bile ducts are more resistant to hepatobiliary injury than large mouse cholangiocytes (LGCCs) from large bile ducts. The definitive endoderm marker, forkhead box A2 (FoxA2), is the key transcriptional factor that regulates cell differentiation and tissue regeneration. Our aim was to characterize the translational role of FoxA2 during cholestatic liver injury. Messenger RNA expression in SMCCs and LGCCs was assessed by polymerase chain reaction (PCR) array analysis. Liver tissues and hepatic stellate cells (HSCs) from primary sclerosing cholangitis (PSC) and primary biliary cholangitis (PBC) patients were tested by real‐time PCR for methylation, senescence, and fibrosis markers. Bile duct ligation (BDL) and multidrug resistance protein 2 (MDR2) knockout mice (MDR2 –/– ) were used as animal models of cholestatic liver injury with or without healthy transplanted large or small cholangiocytes. We demonstrated that FoxA2 was notably enhanced in murine liver progenitor cells and SMCCs and was silenced in human PSC and PBC liver tissues relative to respective controls that are correlated with the epigenetic methylation enzymes, DNA methyltransferase (DNMT) 1 and DNMT3B. Serum alanine aminotransferase and aspartate aminotransferase levels in nonobese diabetic/severe combined immunodeficiency mice engrafted with SMCCs post‐BDL showed significant changes compared to vehicle‐treated mice, along with improved liver fibrosis. Enhanced expression of FoxA2 was observed in BDL mouse liver after SMCC cell therapy. Furthermore, activation of fibrosis signaling pathways were observed in BDL/MDR2 –/– mouse liver as well as in isolated HSCs by laser capture microdissection, and these signals were recovered along with reduced hepatic senescence and enhanced hepatic stellate cellular senescence after SMCC engraft. Conclusion: The definitive endoderm marker and the positive regulator of biliary development, FoxA2, mediates the therapeutic effect of biliary‐committed progenitor cells during cholestatic liver injury. (Hepatology 2017;65:544‐559).